Pemanfaatan Limbah Minyak Jelantah Menjadi Sabun Cuci Piring sebagai Alternatif Usaha Masyarakat di Desa Karya Indah Kecamatan Tapung Kampar - Yunita, Imelda; Siregar, Erpiani; Resdati, Resdati; Dewi, Yossie Kharisma; Diana, Ayu (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Cooking oil is one of the basic necessities in all households in Indonesia. This commodity must always be available because cooking oil is used to process daily food such as frying and stir-frying. The use of cooking oil in household needs is high because it is commonly used for frying. People in Karya Indah Village often use cooking oil repeatedly for frying. The consumable cooking oil is usually disposed of immediately and no further processing is carried out. The immediate environmental impact is the blockage of waterways and the potential for soil pollution. For this reason, it is necessary to make an innovation to used cooking oil that does not pollute the environment when disposed of and has economic value in the community. Community Partnership Empowerment (PKM) activities were carried out in Perum. Gravindo 1, Tapung District, Kampar Regency, Riau. This activity was attended by 10 housewife partners, 3 lecturers and 2 students. This activity consists of three stages, namely the first stage of demonstration of how to refine used cooking oil, the second stage of socialization to residents and the third stage of making dish soap. The resulting product is in the form of dish soap with the use of used cooking oil in its manufacture. This training received a positive response and provided knowledge and skills benefits to housewife partners. The dish soap that has been made can be applied to clean dirt on dishes.